The influence of internal control, leadership style, and teamwork to information system project success - Gui, Anderes; Fernando, Yudi; Aditya Septiani, Wiwoho; Bambang, Leo Handoko; Hasnah, Haron (KnE Social Sciences, 2019)
The purpose of this research is to investigate the influence of internal control, leadership style, and teamwork on the success of the information technology projects. The method of data collection is done by studying literature, questionnaires, interviews, and direct field observations. The research methodology used is quantitative method with the primary and secondary data source. Questionnaires were distributed to the project team, and 110 responses of employees at AIT Co. were received. Data were analyzed using IBM SPSS. Findings showed that internal control and teamwork have a significant influence on the success of the information technology projects, but leadership style not significant. It was found that internal control, leadership style, and teamwork simultaneously have a significant and positive influence on the information technology projects success by 80%. The implication of this study is to increase successful project rate, the role of internal control is important to monitor from the earliest stage until project finished, and company needs to arrange program such as watch together, eat together or outing program. For future research is to expand the scope of the study, such as increasing the number of companies involved, with variations in other variables and can add control and moderating variables.